2014
DOI: 10.2174/1573399809666131126152044
|View full text |Cite
|
Sign up to set email alerts
|

Momordica charantia and Type 2 Diabetes: From in vitro to Human Studies

Abstract: Type 2 diabetes is a growing health problem worldwide that is particularly severe in India and China. In these areas, bitter gourd (Momordica charantia) is a popular vegetable which is traditionally known to have health beneficial effects not only, but mainly, on diabetes. Bitter gourd could be a cheap possibility to help the poor in these and other countries to control their blood glucose levels. This review describes anti-diabetic effects of bitter gourd reported in the literature and discusses what still ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Fu‐Zhu‐Jiang‐Tang (FZJT) tablet, which consists of six well‐known traditional Chinese medicines – Pueraria lobata (PL), Morus alba (MA), Panax notoginseng (PN), Astragalus membranaceus (AM), Momordica charantia (MC) and Cortex lycii (CL) – has been proven to show beneficial effects on patients with type II diabetes. A number of articles have been published on the traditional use of the six individual herbs for the treatment of diabetes (Habicht, Ludwig, Yang, & Krawinkel, ; Li, Wang, Xue, Gu, & Lin, ; Ulbricht et al, ; Uzayisenga, Ayeka, & Wang, ; Zhang, Pugliese, Pugliese, & Passantino, ). For instance, the nonanthocyanin phenolics of MA known to date are rutin, quercetin and 2‐caffeoylquinic acid isomers, which exhibit anti‐diabetic effects through inhibition of α ‐glucosidase (Zhang, Han, He, & Duan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fu‐Zhu‐Jiang‐Tang (FZJT) tablet, which consists of six well‐known traditional Chinese medicines – Pueraria lobata (PL), Morus alba (MA), Panax notoginseng (PN), Astragalus membranaceus (AM), Momordica charantia (MC) and Cortex lycii (CL) – has been proven to show beneficial effects on patients with type II diabetes. A number of articles have been published on the traditional use of the six individual herbs for the treatment of diabetes (Habicht, Ludwig, Yang, & Krawinkel, ; Li, Wang, Xue, Gu, & Lin, ; Ulbricht et al, ; Uzayisenga, Ayeka, & Wang, ; Zhang, Pugliese, Pugliese, & Passantino, ). For instance, the nonanthocyanin phenolics of MA known to date are rutin, quercetin and 2‐caffeoylquinic acid isomers, which exhibit anti‐diabetic effects through inhibition of α ‐glucosidase (Zhang, Han, He, & Duan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Momordica charantia L. Antidiabetic: while a number of preclinical and clinical studies suggest antidiabetic activity (Habicht et al, 2014), the four RCTs standing up to the quality criteria of a recent Cochrane review found limited efficacy in glycaemia control, the risk of bias being high in all four studies (Ooi et al, 2012). A newer systematic review and meta-analysis evaluating 10 clinical studies, however, concluded that different M. charantia preparations improved glycemic control in T2DM patients but based on low quality evidence for the primary outcomes (Peter et al, 2019) A placebo-controlled, double-blind trial with T2DM patients showed that the application of 2,000 mg dried fruit pulp/d over 3 months decreased a range of parameters associated with diabetes such as BW, BMI, waist circumference, fat percentage, glycated hemoglobin A1c, 2-h glucose in the oral glucose tolerance test and glucose in parallel to an increase in insulin secretion (Cortez-Navarrete et al, 2018).…”
Section: Safe and Effective D27mentioning
confidence: 99%
“…It is also used as an antioxidant, antispasmodic, anticholinergic and antiulcerogenic agent to treat gastric and malignant ulcers (Wu et al, 2007;Ozbakis Dengiz et al, 2005). Today, the antidiabetic properties of M charantia are being largely studied and confirmed (Habicht et al, 2014).…”
Section: Species Used In Traditional Medicinementioning
confidence: 99%